2010
DOI: 10.1111/j.1365-313x.2010.04324.x
|View full text |Cite
|
Sign up to set email alerts
|

Two LysM receptor molecules, CEBiP and OsCERK1, cooperatively regulate chitin elicitor signaling in rice

Abstract: Chitin is a major molecular pattern for various fungi, and its fragments, chitin oligosaccharides, are known to induce various defense responses in plant cells. A plasma membrane glycoprotein, CEBiP (chitin elicitor binding protein) and a receptor kinase, CERK1 (chitin elicitor receptor kinase) (also known as LysM-RLK1), were identified as critical components for chitin signaling in rice and Arabidopsis, respectively. However, it is not known whether each plant species requires both of these two types of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
585
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(621 citation statements)
references
References 35 publications
7
585
0
13
Order By: Relevance
“…In the situation of defence responses to pathogenic fungi, LysM RLK1 (Wan et al 2008) or CERK1 (Miya et al 2007)/CERK1 (as in Arabidopsis ) or CERK1/CEBiP receptor dimers (as in rice, Shimizu et al 2010) needs longer chito-oligomers, like octamers to activate its response through heterodimerisation (Hayafune et al 2014; Liu et al 2015). The perception of shorter oligosaccharides such as chitotetraose could instead rely on monomeric receptors (Miyata et al 2014; Shinya et al 2015) as into each receptor’s LysM domain, half of this oligomer molecule (C4) fits (Liu et al 2012; Shinya et al 2015).…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
“…In the situation of defence responses to pathogenic fungi, LysM RLK1 (Wan et al 2008) or CERK1 (Miya et al 2007)/CERK1 (as in Arabidopsis ) or CERK1/CEBiP receptor dimers (as in rice, Shimizu et al 2010) needs longer chito-oligomers, like octamers to activate its response through heterodimerisation (Hayafune et al 2014; Liu et al 2015). The perception of shorter oligosaccharides such as chitotetraose could instead rely on monomeric receptors (Miyata et al 2014; Shinya et al 2015) as into each receptor’s LysM domain, half of this oligomer molecule (C4) fits (Liu et al 2012; Shinya et al 2015).…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
“…Shimizu et al has found that a major portion of CEBiP proteins were visualized as homodimers by the blue native PAGE analysis. 13 However, a small fraction of CEBiP proteins did exist as larger-size oligomers, 13 which may suggest that some CEBiP proteins can be in the same complexes with OsLYP4 and OsLYP6. Our data that CEBiP interacted with OsLYP4 in yeast and in plant cells (Fig.…”
Section: Oslyp4 and Oslyp6 May Cooperate With Other Lysm-containing Rmentioning
confidence: 99%
“…2A, and reviewed in ref. 13), and these OsLYPs apparently need a signaling partner (e.g., OsCERK1) 13 with an intracellular kinase domain for defense signal transduction, the composition and the stoichiometry of different chitin or PGN receptor complexes in rice await further investigation, which will shed new light on the rice innate immunity.…”
Section: Oslyp4 and Oslyp6 May Cooperate With Other Lysm-containing Rmentioning
confidence: 99%
“…The receptor-like kinase BAK1 functions as a coreceptor of FLS2 and EFR in the perception of bacterial flagellin and translation elongation factor EF-Tu (Chinchilla et al, 2007;Heese et al, 2007;Schulze et al, 2010;Roux et al, 2011). In rice (Oryza sativa), CERK1 functions together with the lysin motif (LysM) domain protein CEBiP to recognize the fungal cell wall component chitin (Shimizu et al, 2010). Together with two other LysM domain proteins, LYM1 and LYM3, Arabidopsis (Arabidopsis thaliana) CERK1 is also involved in the perception of bacterial peptidoglycan (Willmann et al, 2011).…”
mentioning
confidence: 99%